We would never : a novel - Mirvis, Tova (Avid Reader Press, 2025)
"When Hailey Gelman becomes a suspect in her ex-husband Jonah's murder following a bitter custody battle, her tight-knit family--including her fiercely protective mother, brother, and secretive father--must confront their own dark loyalties and the lengths they will go to protect each other"--